Pengaruh Tangible dan Empathy Terhadap Kepuasan Konsumen pada PT.Trans Armada Indonesia, Jakarta Utara - Putri Dhea Jasmine (Jurnal Publikasi Ilmu Manajemen, 2024)
The car rental business in Indonesia is one kind of industry that can survive in the midst of the problems that exist even though it has experienced a decline in small cities to big cities as well. One of them is the Trans Fleet of Indonesia, North Jakarta, which is able to get out of the crisis of the Covid-19 pandemic to the present day. This research aims to identify and analyze the impact of Tangible and Empathy on consumer satisfaction with the object of research on consumers PT. Trans Armada Indonesia, North Jakarta. The study uses a quantitative approach with a questionnaire of 138 respondents using the SPSS Version 25 analytical tool. The results in this study showed that Tangible and Empathy influenced consumer satisfaction by 66.1% obtained from R Square results and the remaining 33.9% Consumer Satisfaction was affected by other variables not described in the study.